Implementation Of The Spiritual Values Of Ustaz Neezam Al Banjari In Community Life - Siti Nurul Azida Binti Mohd Noor Ajiba; Syawaluddin Nasution (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study examines how spiritual values articulated by Ustaz Neezam Al-Banjari are translated into lived social practices within a contemporary Malaysian community. While spirituality in Islam emphasizes the integration of devotion and social responsibility, its internalization does not automatically generate transformative social behavior. Using a qualitative case study design, this research explores how salawat-centered da‘wah is internalized and embodied within Raudhah Muhibbin (Dewan Selawat Taman Mahabbah). Data were collected through semi-structured interviews, participant observation, and document analysis, involving fourteen informants selected purposively. The findings reveal five interconnected spiritual orientations: devotion through salawat, lived simplicity, inclusive ukhuwah, communicative adab, and social responsibility. Salawat functions as an affective mechanism shaping emotional regulation and moral awareness. Simplicity fosters relational legitimacy, while inclusive gatherings strengthen communal solidarity. Emphasis on adab moderates social interaction, and spiritual devotion is externalized through collective service initiatives. The study concludes that spiritual leadership becomes socially transformative when emotional internalization, relational trust, and embodied ethical practice converge within sustained communal engagement.